International Student Recruitment in a Post-China World - Esaki-Smith, Anna (International Higher Education, 2020)
Growth in Chinese student flows to the major English-language study destinations has slowed considerably since 2016. A number of factors are contributing to this trend, including an aging demographic, slower economic expansion in China, and the emergence of less expensive overseas study options. What will international student recruitment look like, as universities adjust to a “post-China” world?